2014
DOI: 10.1128/jcm.01683-14
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Cryptococcal Meningitis by Use of Lateral Flow Assay on Cerebrospinal Fluid Samples: Influence of the High-Dose “Hook” Effect

Abstract: e Cryptococcal meningitis is the most frequent cause of meningitis and a major cause of mortality in HIV-infected adults in Africa. This study evaluated the performance of the lateral flow assay (LFA) on cerebrospinal fluid (CSF) samples for the diagnosis of cryptococcal meningitis against that of existing diagnostic tests. LFA performed on 465 undiluted CSF samples had a sensitivity of 91%. When the LFA was paired with Gram staining, a sensitivity of 100% was achieved after implementation of a dilution step f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…A more recent multisite diagnostic study in Uganda and South Africa found the CrAg LFA to have a sensitivity and specificity of 99.3% and 99.1% in CSF (6). In a study published in South Africa, the sensitivity of the CrAg LFA in CSF was reported as only 91% (11); however, when samples with a suspected high organism load underwent a 1:2 dilution prior to testing, sensitivity improved to 100%, an incongruity attributed to the “hook effect”, whereby a high cryptococcal antigen load interferes with the antigen-antibody complex of the assay producing false negative results.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent multisite diagnostic study in Uganda and South Africa found the CrAg LFA to have a sensitivity and specificity of 99.3% and 99.1% in CSF (6). In a study published in South Africa, the sensitivity of the CrAg LFA in CSF was reported as only 91% (11); however, when samples with a suspected high organism load underwent a 1:2 dilution prior to testing, sensitivity improved to 100%, an incongruity attributed to the “hook effect”, whereby a high cryptococcal antigen load interferes with the antigen-antibody complex of the assay producing false negative results.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for exclusion as shown in Figure 1. Finally, we included 15 quali ed articles [9,11,[13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Search Resultsmentioning
confidence: 99%
“…18 studies were excluded after screening the abstracts. After full-text review, we included 15 qualified articles [9][10][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Search Resultsmentioning
confidence: 99%